Recapturing the nature and visual of padang in the historic cities in Malaysia - Harun, Nor Zalina (IIUM Press, 2015)
This chapter reveals the argument that while other categories of physical functions should be emphasized, the visual aspects of public space cannot be neglected. This chapter therefore delves into reviews on two long existed public spaces locally known as padang. For this purposes, two padang of historical cities in Malaysia were reviewed. This chapter starts with general information of public spaces in the historic city in Malaysia and their long established qualities and attributes. Drawing upon the study, the chapter draws attention to history and significance of Padang Club Selangor, Kuala Lumpur and Padang Kota Lama, Penang.